U.S.-China Trade Relations in the Biden Era: Trade War, Industrial Policy, and Rule-Based International Order. (2021) - Jiangyu, Wang; Hewett, Dawn Yamane
Abstract : Presidential candidate Joe Biden's team declared President Trump's trade war with China a failure when Democratic nominee Senator Kamala Harris told Vice President Mike Pence at the U.S. vice presidential debate that "You lost that trade war." Half a year has passed since Biden took over the White House, the U.S.-China trade war is still going on, though in a much less pompous manner than what President Donald Trump once liked it to be. President Biden refused to make significant change to Trump's tough stance on U.S.-China trade relations on the ground of the accusations of China's "stealing" intellectual property (IP), state subsidies to enterprises, forced technology transfer from foreign companies, among others. On the other hand, China has not backed off from the trade war, though it arguably made many concessions in the so-called "Phase 1 trade deal" signed by the United States and China on January 15, 2020, in which China pledged to buy US 200 billion more of American goods and services in 2020 and 2021, in addition to the commitments to strengthen protection and remove forced technology transfer. Evidence suggested that China was still far behind prorated targets of a full year when Biden assumed presidency in January 2021. More significantly, Chinese President Xi Jinping has been taking the opportunities offered by the trade war to remake the Chinese economy toward state capitalism. Additionally, as the trade war was happening, the Trump administration intensified its assault on the multilateral trading system under the World Trade Organization (WTO) and effectively paralyzed the Appellate Body, a crucial part of the WTO's Dispute Settlement System.